An Empirical Study of the Performance Persistence of China's Equity Open-end Funds - Li, Jin (2007)
Mutual funds performance persistence is an abnormality of Efficient Market Hypothesis (EMH). It means better performer funds in period one will continue to perform better in successive periods, while worse performer funds in period one will keep losing value in successive periods (Hendricks, Patel and Zeckhauser, 1997).